Impact of transformational leadership capability on employee motivation in the public sector at state human resource unit in Chief Minister department of Sarawak/ Rody Bunsu - Bunsu, Rody (2016)
Leader play very important role in building and sustainable business and community in organization. Leadership style is one of the important factor that can affect motivation. Therefore this study is to examine the impacts of Transformational Leadership Capability on the employee's motivation in the Public Sector at State Human Resource Unit in Chief Minister Department of Sarawak. The study use primary data, using random sampling, 130 questionnaires were distributed, out of which 108 were completed. The questionnaire contains different elements drawn from a) Transformational Leadership adopted and modified from Jeevan Jyoti and Manisha Dev (2016) and b) Motivation adopted and modified from Tan Teck - Hong and Amna Waheed (2011). For transformational leadership capability and employee motivation, all the items arranged in degree of agreement by a 7 point likert scale. 7 point likert scale. Data were analyzed by reliability analysis, descriptive statistics. Correlation and regression analysis to complete the research objective. The study reveals that there strong relationship between intellectual stimulation and inspirational motivation with employees motivation and moderate relationship between idealized influence and individualized consideration with employees motivation.